Automatic imitation in dogs - Range, Friederike (The Royal Society, 2011)
After preliminary training to open a sliding door using their head and their paw, dogs were given a discrimination task in which they were rewarded with food for opening the door using the same method (head or paw) as demonstrated by their owner (compatible group), or for opening the door using the alternative method (incompatible group). The incompatible group, which had to counterimitate to receive food reward, required more trials to reach a fixed criterion of discrimination performance (85% correct) than the compatible group. This suggests that, like humans, dogs are subject to ‘automatic imitation’; they cannot inhibit online the tendency to imitate head use and/or paw use. In a subsequent transfer test, where all dogs were required to imitate their owners' head and paw use for food reward, the incompatible group made a greater proportion of incorrect, counterimitative responses than the compatible group. These results are consistent with the associative sequence learning model, which suggests that the development of imitation depends on sensorimotor experience and phylogenetically general mechanisms of associative learning. More specifically, they suggest that the imitative behaviour of dogs is shaped more by their developmental interactions with humans than by their evolutionary history of domestication.